2014
DOI: 10.1128/mbio.01098-14
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Evolutionarily Distinct Avian Influenza A Viruses in Antarctica

Abstract: Distinct lineages of avian influenza viruses (AIVs) are harbored by spatially segregated birds, yet significant surveillance gaps exist around the globe. Virtually nothing is known from the Antarctic. Using virus culture, molecular analysis, full genome sequencing, and serology of samples from Adélie penguins in Antarctica, we confirmed infection by H11N2 subtype AIVs. Their genetic segments were distinct from all known contemporary influenza viruses, including South American AIVs, suggesting spatial separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
3
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 58 publications
5
84
3
11
Order By: Relevance
“…After 21 days, blood was collected to test for seroconversion by HI assay with turkey red blood cells 37, 38. The HI assay was conducted in triplicate, and the titers are reported as the geometric means.…”
Section: Methodsmentioning
confidence: 99%
“…After 21 days, blood was collected to test for seroconversion by HI assay with turkey red blood cells 37, 38. The HI assay was conducted in triplicate, and the titers are reported as the geometric means.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the early studies have relied on serological assays for identifying putative paramyxoviruses, orthomyxoviruses, flavirviruses and birnaviruses in wild penguin populations (Alexander et al, 1989;Austin & Webster, 1993;Gardner et al, 1997;Miller et al, 2010;Morgan et al, , 1985Smith et al, 2008;Thomazelli et al, 2010) and herpesviruses and togaviruses in captive individuals (Kincaid et al, 1988;Tuttle et al, 2005). A handful of recent studies have identified some of the viruses (avipoxviruses, Newcastle disease viruses, adenovirus, avian influenza virus and papillomavirus) at a molecular level (Carulei et al, 2009;Hurt et al, 2014;Kane et al, 2012;Lee et al, 2014;Thomazelli et al, 2010;Varsani et al, 2014).…”
mentioning
confidence: 99%
“…To the best of our knowledge, this is one of the five genomes of viruses associated with Antarctic animals to be characterized to date; previously identified viral genomes include those of a P. adeliae papillomavirus and an avian influenza virus subtype H11N2 from Adélie penguins (Hurt et al, 2014;Varsani et al, 2014) and adenoviruses from South Polar skuas and chinstrap penguins (Pygoscelis antarctica) (Lee et al, 2014;Park et al, 2012). This highlights the poor knowledge of viruses associated with Antarctic animals.…”
mentioning
confidence: 99%
“…For instance, recent studies have found that penguins (Sphenisciformes) play an important role along with Charadriiformes in the persistence and evolution of AIV in Antarctica, a dynamic that could not have been witnessed in studies conducted in the Northern Hemisphere since penguins do not occur there. 29,30 Inversely, murres and auklets (Alcidae) play an important role in AIV transmission in the Northern Hemisphere but are absent in the Southern Hemisphere. 31,32 Furthermore, even though it is reasonable to consider aquatic birds as prime candidates for AIV surveillance in South America, the role of terrestrial birds as reservoirs of AIV should not be dismissed.…”
Section: Recent Studies Of Aiv In South Americamentioning
confidence: 99%